Clinically relevant antibiotic resistance in Escherichia coli from black kites in southwestern Siberia: a genetic and phenotypic investigation - Tarabai, Hassan; Krejci, Simon; Karyakin, Igor; Bitar, Ibrahim; Literak, Ivan; Dolejska, Monika (mSphere, 2023)
Wild birds including raptors can act as vectors of clinically relevant bacteria with antibiotic resistance. The aim of this study was to investigate the occurrence of antibiotic-resistant Escherichia coli in black kites (Milvus migrans) inhabiting localities in proximity to human-influenced environments in southwestern Siberia and investigate their virulence and plasmid contents. A total of 51 E. coli isolates mostly with multidrug resistance (MDR) profiles were obtained from cloacal swabs of 35 (64%, n = 55) kites. Genomic analyses of 36 whole genome sequenced E. coli isolates showed: (i) high prevalence and diversity of their antibiotic resistance genes (ARGs) and common association with ESBL/AmpC production (27/36, 75%), (ii) carriage of mcr-1 for colistin resistance on IncI2 plasmids in kites residing in proximity of two large cities, (iii) frequent association with class one integrase (IntI1, 22/36, 61%), and (iv) presence of sequence types (STs) linked to avian-pathogenic (APEC) and extra-intestinal pathogenic E. coli (ExPEC). Notably, numerous isolates had significant virulence content. One E. coli with APEC-associated ST354 carried qnrE1 encoding fluoroquinolone resistance on IncHI2-ST3 plasmid, the first detection of such a gene in E. coli from wildlife. Our results implicate black kites in southwestern Siberia as reservoirs for antibiotic-resistant E. coli. It also highlights the existing link between proximity of wildlife to human activities and their carriage of MDR bacteria including pathogenic STs with significant and clinically relevant antibiotic resistance determinants. IMPORTANCE Migratory birds have the potential to acquire and disperse clinically relevant antibiotic-resistant bacteria (ARB) and their associated antibiotic resistance genes (ARGs) through vast geographical regions. The opportunistic feeding behavior associated with some raptors including black kites and the growing anthropogenic influence on their natural habitats increase the transmission risk of multidrug resistance (MDR) and pathogenic bacteria from human and agricultural sources into the environment and wildlife. Thus, monitoring studies investigating antibiotic resistance in raptors may provide essential data that facilitate understanding the fate and evolution of ARB and ARGs in the environment and possible health risks for humans and animals associated with the acquisition of these resistance determinants by wildlife.
Keywords: Animals; Birds; antagonisté receptorů pro angiotenzin; Escherichia coli; Sibiř; inhibitory ACE; divoká zvířata; lidé; Anti-Bacterial Agents; Angiotensin-Converting Enzyme Inhibitors; proteiny z Escherichia coli; ptáci; Siberia; Animals, Wild; mnohočetná bakteriální léková rezistence; Drug Resistance, Multiple, Bacterial; zvířata; Angiotensin Receptor Antagonists; antibakteriální látky; Escherichia coli Proteins; Humans